STRATEGI KEPALA MADRASAH DALAM PENINGKATAN MUTU PADA LEMBAGA PENDIDIKAN DI KELOMPOK KERJA MADRASAH ALIYAH (KKMA) 03 KABUPATEN BANDUNG - Meranti Sylvitiani; Nan Rahminawati; Ayi Sobarna (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
In the Society 5.0 Era, which emphasizes the integration of smart technology and human-centered values, along with the implementation of the Merdeka Curriculum that demands differentiated and student-centered learning, enhancing the quality of madrasah education has become a strategic effort to develop graduates who are adaptive, competitive, and excel spiritually and intellectually. This research aims to explore the leadership strategies of madrasah principals in improving institutional quality through the formulation of contextual vision and mission, the establishment of prioritized quality improvement programs, and the implementation of data-driven evaluation strategies. The study was conducted at several Madrasah Aliyah under the Working Group of Islamic Senior High Schools (KKMA 03) in Bandung Regency, purposively selected due to their diverse and dynamic quality improvement practices. A qualitative approach with a descriptive method was employed. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that principals play a crucial role in shaping institutional direction through visionary and contextualized mission statements. The prioritized program steps were developed based on needs analysis and aligned with the eight National Education Standards. Program evaluation was carried out systematically and continuously using the CIPP model (Context, Input, Process, Product), Kirkpatrick, and logic model. This study confirms that the leadership strategy of madrasah principals significantly contributes to holistic and sustainable improvements in educational quality.